Maritime legal labour: empowering workers at sea - Ogola, Eric K Okumu (Institute of Marine and Environmental Law, 2023)
In the popular mind the principle of equality before the law is sometimes confused with the idea that the law applies to every one in the same way. But there are certain groups of workers who are excluded for one reason or another from many of the benefits or burdens of legislation passed by Parliament to regulate or improve behaviour in certain areas of life, or to whom such legislation applies in a peculiar way. In the field of employment and labour law, those who work on the seas as seamen belong to such groups.